(untitled) - Reininger, Stuart (Camden, Me., 2008)
With no secondary method of propulsion, poorer stability profiles, and enough speed to get themselves into trouble fast, powerboats are far more susceptible to emergencies than sailboats. Confident Powerboating addresses your safety concerns, providing a detailed guide to avoiding problems, coping with difficult situations, and responding to emergencies effectively.
Keywords: Motorboats,Boats and boating,Xuồng máy,Thuyền và chèo thuyền